Cloning and Expression of Vp2 Gene of Chicken Anemia Vurus Strain Cux-1 in Lactococcus Lactis Mg1363 - Ahmat, Nurfilza (2001)
In this study, the lactococcal plasmid vector pMG36e, was exploited for the cloning, replication and expression of a viral protein-2 (VP2) gene in the bacterial host, Lactococcus lactis strain MG1363. The VP2 gene (0.65 kb) of chicken anemia virus (CAV) of strain Cuxhaven-l was amplified from viral genomic DNA by polymerase chain reaction (PCR) using the VP2FX and VP2RSai primers (Table 6), cloned into the expression vector pMG36e, and electrotransformed into the L. lactis MG1363 host. Sequencing of the recombinant plasmid pMG36e-VP2 using the Forward and Reverse primers (Table 6), showed 99% homology of the VP2 insert with that of the published VP2 CAY Cux-l sequence. SDS-PAGE and Western blot hybridization of L. lactis (pMG36e-VP2; 4.3 kb), showed no significant protein band of VP2 gene product (24 kDa). However, the gene was transcribed under the P32 promoter of the expression vector pMG36e as shown by a 0.7 kb reverse-transcribed product of the VP2 gene.